Spatio-temporal analysis and estimation of rainfall variability in and around upper Godavari River basin, India - Gawali, Praveen; Lakshmi, B V (My University, 2019)
Spatio-temporal analysis and estimation of rainfall variability is an important factor to characterize the hydrological manifestation for precise water management. Fifteen years’ daily rainfall data (2000–2014) of 39 rain gauge stations (RGS), situated in and around upper Godavari basin (UGB), was analyzed using statistical computations. Mean annual rainfall (MAR) and mean halfdecadal rainfall, along with standard deviation (SD), coefficient of variation (CV), standardized anomaly (SA), mean absolute deviation (MAD), and spatial distribution of rainfall (SDR), were computed to delineate the orographic effect, if any, over rainfall. Box and whisker diagrams display rainfall distribution. The analyzed data was incorporated in Geographical Information System (GIS) software, and spatial estimation of half-decadal rainfall, SA, and SDR carried out using inverse distance weighting (IDW) interpolation method. RGS mean rainfall of 2000–2004, 2005–2009, and 2010–2014 were correlated with satellite-derived Tropical Rainfall Measuring Mission (TRMM) data using Pearson correlation coefficient (R) to confirm the accuracy and validity of both the data. Statistical results and spatial estimation of rainfall indicate high spatio-temporal variability during 2010–2014 and lower during 2005–2009. Monsoon intensity revealed increasing trend from 2000 to 2006, which was seen to be decreasing later, with rise and fall from 2006 to 2014. The rainfall was seen to increase towards west due to an obstruction posed by theWestern Ghat to the east flowing monsoon wind. Strong positive correlation was found between TRMM and 3 half-decade rainfall data. The approach adopted in this paper identified the micro level rainfall variability which will be greatly advantageous for sustainable water resource management.
Keywords: Rainfall variability, GIS, Spatio-temporal estimation, Watermanagement